Customer experience and satisfaction: a case study of e-Filing service by IRB Malaysia / Syed Ahmad Faisal Othman - Othman, Syed Ahmad Faisal (2009)
This study is entitled “CUSTOMER EXPERIENCE AND SATISFACTION: A CASE STUDY OF e-FILING SERVICE BY IRB MALAYSIA”. As nowadays, Inland Revenue Board (IRB) Malaysia has organized e-Filing service for their tax payers to submit their tax forms through online. This study is look forward to analyze the level of experience and satisfaction for their users towards this service. As part of that, a feedback from the respondents are taken and analyzed by the researcher. The significant of this study will give good impact firstly to Inland Revenue Board Malaysia, then to the respondents and lastly to the researcher as well. Two types of data collection method are used. There are primary data and secondary data. Where primary data in this research, questionnaires will be design in order to guide researcher to interview respondents and secondary data are information, which are already in existences, but are relevant to this study. Two types of secondary were used. There are internal and external secondary data. Internal sources are those data is gathered within the organization that the research had carried out. These include information that collected from magazines, newspaper, pamphlets and others. External sources are those data that is collected outside the organization. These include data that is gathered from Internet, projects paper and other published document from libraries. Based on the analysis, the researcher had found the conclusion and some recommendation towards the e-Filing service.